Between Islamic Education Core Values and Character Building - Risnita Risnita; Dian Cita Sari (IJER (Indonesian Journal of Educational Research), 2020)
The purpose of this study is to know the relation between Islamic education core values and character building. Islamic education has a value meaning with a very deep influence, as formulated from the Quran, As-Sunnah and leading contemporary Muslim scholars. The major basic principles of Islamic education core value to character building which are considered as very important in this contemporary Muslim world are knowledge, tawhid (Oneness of God), vicegerent of Allah, Taqwa or God-Fearing, and, effort to persuade good deeds and prohibit evil among subordinates and community. In fact, other principles are amanah (trust), justice, shura (consultation), brotherhood, moral and ethical behaviours, responsibility (trustworthiness), muhasabah (accountability) and motivation. Islamic education can cultivate positive perceptions and motivations, positive emotional responses, and can avoid stress reactions. Its special Islamic education core value is the tawhid (unity) which is the spiritual and material unity, the unity of body and soul, the unity of the world and the hereafter, and the unity of thought and action. Because individuals have different concepts of what is right, it is necessary to develop core values of Islamic education for character building. Method of this study is descriptive qualitative. Result of this study are Islamic education core values (Tawhid) is a process of inspiring and coaching voluntary followers in an effort to fulfil a clear as well as shared vision